2007
DOI: 10.1016/j.exer.2006.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Classical complement activation and acquired immune response pathways are not essential for retinal degeneration in the rd1 mouse

Abstract: Misregulation of the innate immune response and other immune-related processes have been suggested to play a critical role in the pathogenesis of a number of different neurodegenerative diseases, including age related macular degeneration. In an animal model for photoreceptor degeneration, several genes of the innate and acquired immune system were found to be differentially regulated in the retina during the degenerative process. In addition to this differential regulation of individual genes, we found that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…36 It has been shown in genetic studies that lack of functional B and T cells or of complement factor C1q␣ has no impact on the progression of photoreceptor cell loss in rd1 mice, suggesting that the classic complement system of innate immunity and acquired immune responses may not be implicated. 75 Yet, these observations and the fact that Sn is not expressed in retinal macrophages in the two models studied should not be taken as definitive indication that immune-related events do not contribute to photoreceptor cell loss.…”
Section: Sn and Retinal Transplantationmentioning
confidence: 89%
“…36 It has been shown in genetic studies that lack of functional B and T cells or of complement factor C1q␣ has no impact on the progression of photoreceptor cell loss in rd1 mice, suggesting that the classic complement system of innate immunity and acquired immune responses may not be implicated. 75 Yet, these observations and the fact that Sn is not expressed in retinal macrophages in the two models studied should not be taken as definitive indication that immune-related events do not contribute to photoreceptor cell loss.…”
Section: Sn and Retinal Transplantationmentioning
confidence: 89%
“…In support of this hypothesis, we show that in the absence of C1q, cone photoreceptor viability and function are significantly compromised. It is of interest to note that in an elegant study, Rohrer et al 53 have recently reported that photoreceptor degeneration in the rd1 mouse, with a naturally occurring null mutation within the gene encoding the b-subunit of cyclic GMP phosphodiesterase, is unaffected in the absence of C1q. However, no ERG studies on cone cell function were reported in that study, and the rapidity of retinal degeneration in that model (complete photoreceptor loss within 3 weeks of birth) may have masked any more subtle effects in phenotype that may have been induced by the absence of C1q.…”
Section: Discussionmentioning
confidence: 99%
“…57,58 However, the ablation of C1q␣ in rd1 mice did not appear to delay the removal of apoptotic cells, indicating that the classic pathway-or at least C1q␣-alone may not be sufficient to initiate their clearance. 59 We also showed differential expression of the carbohydrate recognition molecule ficolin B, which promotes the removal of late-stage apoptotic cells through binding to DNA, 60 mediated by the lectin pathway. Upregulation of these genes suggests that a role of complement activation in this model is the efficient removal of apoptotic cells after BCL.…”
Section: A Transcriptional Profile Of Complement Activation After Bclmentioning
confidence: 99%